DNA isolation from processed shrimp food products (shrimp tempura) - Alfi Sophian (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2025)
DNA isolation is an important step that must be carried out in research or testing the identification of DNA species based on molecular techniques using PCR or real-time PCR. The purpose of this study was to determine the quality of DNA isolated from shrimp processed food products in shrimp tempura preparations. One of the benefits of this research is that it can be a source of information and reference for similar research. The method used in this research is the DNA isolation method using the spin column technique. Analysis of the quality of the isolated DNA was based on the parameters of the concentration value and DNA purity measured by a nanophotometer at the ratio of A260/A280. Data analysis was carried out by calculating the average concentration and purity values ​​obtained from measurements using a nanophotometer and then calculating the standard deviation values ​​and comparing them. Based on the results of the research conducted, it was concluded that the DNA isolated from the results showed the value of concentration and purity of DNA which was included in the good DNA category. The results of statistical tests on data uniformity show that the data analyzed in this study are homogeneous.